(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The prevalence of malaria remains a significant threat in Sub-Saharan Africa. The occurrence of drug-resistant strains of Plasmodium in Nigeria underscores the urgent need for novel antimalarial medications. This research aims to assess the effectiveness of Adansonia digitata fruit pod extract against Plasmodium berghei infection in mice; determining the oral median lethal dose (LD50) and identifying phytochemical components using Lorke’s and Evan’s methodologies. The extract was assessed for its antiplasmodial activities against P. berghei-berghei in two murine malaria replicas using both suppressive and curative assays. Statistical analysis was conducted using one-way ANOVA. The LD50 of the extract through oral administration exceeded 5000 mg/kg. The extract contains alkaloids, saponins, flavonoids, phenols, tannins, and anthraquinones. The aqueous fruit pulp extract of A. digitata, when administered at 250, 500, and 1000 mg/kg of doses, exhibited a dose-dependent suppression of parasitemia by 25.70%, 42.57%, and 49.39% respectively compared to the control group, parasitaemia clearance rates was 31.76%, 43.34%, and 56.65% respectively. The parasitaemia clearance with a dosage of 1000 mg/kg was found to be statistically significant (p < 0.05).The reference drug (Chloroquine) administering a dosage of 5 mg/kg yielded a significant result (p < 0.05) parasitaemia clearance of 74.76%. Analysis of the Packed Cell Volume (PCV) levels revealed that those treated with the aqueous fruit pulp extracts of A. digitata at doses of 250, 500, and 1000 mg/kg maintained normal PCV values throughout suppressive and curative experiments. However, the PCV in the control groups was markedly diminished (p < 0.05) after both trials.